2023
DOI: 10.1002/ps.7391
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distancing of crops reduces pest pressure while maintaining conservation biocontrol in oilseed rape

Abstract: BACKGROUNDAgricultural landscapes provide resources for arthropod pests as well as their natural enemies. To develop integrated pest management (IPM) practices, it is important to understand how spatiotemporal location influences crop colonization and damage severity. We performed a 3‐year (2016–2018) field experiment in winter oilseed rape (OSR, Brassica napus) fields in Estonia, where half of the fields were within 500 m of the location of the previous year's winter OSR field and half were outside this zone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 84 publications
5
10
0
Order By: Relevance
“…S4). Like Sulg et al, 11 we found the distance to the previous year's closest OSR field to influence cabbage CSW infestation rate (Table 4). In 2 out of 3 years Sulg et al found pod damage in fields with the previous year's closest field located more than 500 m from the current year's OSR field to be smaller than in fields with closest field located within 500 m (0.88% vs 3.28% and 14.18% vs 20.58%, respectively).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…S4). Like Sulg et al, 11 we found the distance to the previous year's closest OSR field to influence cabbage CSW infestation rate (Table 4). In 2 out of 3 years Sulg et al found pod damage in fields with the previous year's closest field located more than 500 m from the current year's OSR field to be smaller than in fields with closest field located within 500 m (0.88% vs 3.28% and 14.18% vs 20.58%, respectively).…”
Section: Discussionsupporting
confidence: 77%
“…The parasitoids of OSR insect pests have been the object of intense scientific work over the last five decades, resulting in a wealth of detailed knowledge of their biology and ecology, especially of pollen beetle (Brassicogethes aeneus (Fabricius)) [4][5][6] and cabbage stem flea beetle (Psylliodes chrysocephala (Linnaeus), 7,8 but also of the cabbage seed weevil (CSW; Ceutorhynchus obstrictus (Marsham). [9][10][11] However, although farmers are becoming more aware of parasitoid presence and activity 12,13 the concept of protecting the parasitoids naturally present in the field still does not seem to play a decisive role in farmers' spraying decisions, mainly because of the complexity of OSR pest management. There are at least five important OSR pest species, each with its specific parasitoid species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distance decay effects of pest dispersal between growing seasons are thus likely a general phenomenon that could be used for regulation of host specialised pest species. While distance decay effects could also be assumed for top‐down control by specialised parasitoids, parasitisation remained stable independent of distance to the host crop in the previous season in a recent assessment in winter oilseed rape (Sulg et al, 2023).…”
Section: Discussionmentioning
confidence: 99%